Heart Transplantation New Insights in Therapeutic Strategies - Fukushima, Norihide (IntechOpen, 2022)
Since the first heart transplantation was performed by Dr. Christiaan Barnard in South Africa in 1967, there has been steady progress in terms of recipient selection, donor selection and management, surgical technique, preoperative management, immunosuppression, mechanical circulatory support during waiting for heart transplantation, especially in the last two decades. This book presents recent information in the field of heart transplantation. It includes thirteen chapters that address such topics as novel immunosuppression therapy and the role of transplant pharmacists, donor management and intervention for primary graft failure, mechanical circulatory, diagnostic modalities for cardiac allograft vasculopathy, surgical techniques, pediatric heart transplantation, and gene therapy. We hope that readers will find this book a useful resource because of its summarization of relevant details and issues that will facilitate the acquisition of emerging new information in each area of heart transplantation.